Molecular and clinical conditions associated with venous thromboembolism in oncological patients - Micco, P. Di; Amitrano, M.; Niglio, A.; Fontanella, A. (Experimental Oncology, 2006)
The association between cancer and thrombophilia has been known since 1865 since Trousseau described it. However in the last three decades an increased interest has been raised on this issue related to several molecular and condition that are involved in the daily management of oncological patients. This brief review has been focused on molecular conditions underlying cancer acquired thrombophilia then to further clinical aspects inducing thrombophilia in oncological patients such as surgery, chemotherapy, concomitant medical illness and inherited thrombophilia. Связь между опухолевым процессом и гематогенной тромбофилией известна с 1865 г., когда Trousseau впервые дал ее описание.
В последнее время отмечают возрастающий интерес к этой проблеме и связанным с ней молекулярным и клиническим
параметрам, которые учитываются при постоянном наблюдении за больными онкологического профиля. Данный короткий
обзор литературы посвящен характеристике молекулярных факторов, лежащих в основе тромбофилии, возникающей
в процессе развития новообразований, а также другим особенностям клинического течения, индуцирующим тромбофилию
у больных онкологического профиля, таким как хирургическое вмешательство, химиотерапия, сопутствующие осложнения
и наследственная тромбофилия